Remarks on Duffin-Kemmer-Petiau theory and gauge invariance - Lunardi, J. T.; Pimentel, B. M.; Teixeira, R. G.; Valverde, J. S. (Elsevier B.V., 2000)
Two problems relative to the electromagnetic coupling of Duffin-Kemmer-Petiau (DKP) theory are discussed: the presence of an anomalous term in the Hamiltonian form of the theory and the apparent difference between the interaction terms in DKP and Klein-Gordon (KG) Lagrangians. For this, we first discuss the behavior of DKP field and its physical components under gauge transformations. From this analysis, we can show that these problems simply do not exist if one correctly analyses the physical components of DKP field. (C) 2000 Elsevier B.V. B.V. All rights reserved.